Research Analysis of "Kulliyat-e-Majeed Amjad" in the Light of Textual Criticism - Rasul, Abdullah Naeem; Haq, Hafiz Zia Ul; Saher, Azka (sourcecoder, 2024)
Majeed Amjad is, one of the famous names in modern Urdu poetry. Although his selection of poetry was known in his life and after his demire, for the first time Khwaja M.Zakria compiled his poetry by the title ’Kulliyat-e-Majeed Amjad’. Khawaja M.Zakaria is recognized as an educationist, researcher, critic and compiler. He has many books in this regard, but ’Kulliyat-e-Majeed Amjad’ became the reason for his fame. The process of compilation is an arduous enterprise and is bases on extensive research. In this research article, a thorough analysis of ’kulliyat-e-Majeed Amjad’ has been made refering to the principles of literary compilation and to evaluate how to successful Khwaja M.Zakria has been in his compilation of the text.